Coalgebraic methods in computer science : 14th IFIP WG 1.3 International Workshop, CMCS 2018, colocated with ETAPS 2018, Thessaloniki, Greece, April 14-15, 2018, Revised selected papers /: 14th IFIP WG 1.3 International Workshop, CMCS 2018, colocated with ETAPS 2018, Thessaloniki, Greece, April 14-15, 2018, Revised selected papers. (2018) - Unknown
No abstract available